LOCAL ECONOMY EMPOWERMENT THROUGH THE SUSTAINABLE COFFEE KNOWLEDGE FOR COFFEE PROFESSIONALS IN BURAIDAH, SAUDI ARABIA - Kurniawan Arif Maspul; Ahmed Mohammed Akrem; Bassam Bondk (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The crowds of specialty coffee in Saudi Arabia have made this country one of the specialty coffee Meccas in the Middle East. Several national and global events have made Saudi Arabia a country visited by many international coffee professionals and professional coffee workers working in Saudi Arabia. Especially with the 2022 Year of Saudi Coffee, Saudi Arabia has also become a significant player in the coffee value chain in the Middle East, counterbalancing the UAE in its role in the global coffee market. One of the challenges is sustainability in the coffee area in Buraidah, where coffee professionals such as baristas and cup tasters have an essential role in maintaining consistency of presentation skills and customer engagement which are the benchmarks and represent specialty coffee as one of its goals. Therefore, with the curriculum used through the Coffee Skills Program and the Coffee Sustainability Program from the Specialty Coffee Association. The author provides training and counselling to calibrate knowledge in coffee from the skills and behaviour of coffee professionals to achieve sustainability in the coffee value chain area and sustain core business more profound. Moreover, to strengthen the local economy after the Covid-19 pandemic.